ANALISIS SEMIOLOGI ROLAND BARTHES ATAS KATA WASȊLAH DALAM QS. Al-MAIDAH [5]: 35: Sebuah Reinterpretasi bagi Masyarakat Modern - Fandi Husain (STAI AL-ANWAR SARANG, 2024)
The command in Qur’an Surah al-Mā’idah [5]: 35 to pursue a means of attaining proximity to God continues to be a contentious topic among Muslims today. The term wasīlah in this verse has been translated by numerous scholars as qurbah, signifying the act of drawing closer to God by actions that are pleasant to Him. Nonetheless, the text does not delineate the specific actions by which one may attain proximity to Allah. Consequently, an analysis of its language features, contextual background, and modern cultural interpretations is essential for achieving a pertinent understanding. This study seeks to examine the significance of the term wasīlah by concentrating on its linguistic and mythical frameworks. This study utilizes a library research methodology employing a descriptive-analytical framework. The findings reveal that, within the linguistic framework, the term wasīlah is interpreted as an intermediary, pathway, technique, and related connotations. Secondly, given the mythological framework, the significance of wasīlah in QS. al-Mā’idah [5]: 35 as a means of approaching Allah becomes very active. Various methodologies and traditions evidently endorse ritual behaviors, encompassing not only required deeds but also those imparted by spiritual wayfarers (sulūk) who hold specific spiritual ranks (maqām) before Allah, with the objective of achieving His pleasure. This study presents a methodological contribution through a semiological reading model (denotation–connotation–myth) applied to a contentious Qur’anic phrase, which may act as a reference framework for the analysis of other terms in contextual Qur’anic interpretation.